The inclusion of content about gender identity at school: A standpoint from notions on knowledge (Research, Society and Development, 2018)
The issue of inserting content on gender identity in Brazilian schools has entered the agendas of different social groups in recent years, having parts of society classifying it as ideological. In this paper we aim to present one perception to understand the issue departing from notions on knowledge. In this way, we show a basis of what can be called the ideological and thus far we approach what is proposed on the question of gender identity in educational contents. We conclude by not defending a position, however, indicating the legitimacy of such defenses, provided that the discussion isn´t based on the argument of "ideological content".